Developing a timed navigation architecture for hospital delivery robots - Silva, Jorge Bruno (2013)
In hospitals, typical tasks of delivering goods between different locations are usually done by auxiliary staff. With the development of robotic technologies, such tasks can be performed by mobile robots releasing the staff effort to other tasks. In order to successfully complete the tasks of delivering goods inside hospitals, mobile robots should be able to generate trajectories free of collisions. In addition, including timing constraints to the generated trajectories has not been addressed in most current robotic systems, and it is critical in robotic tasks as human-robot interaction. Including timing constraints means to obey to the planned movement time, despite diversified environmental conditions or perturbations. In this paper we aim to develop a navigation architecture with timing constraints based on a mesh of nonlinear dynamical systems and feedthrough maps for wheeled mobile robots. A simulated hospital environment and a wheeled robot pioneer 3-DX are used to demonstrate the robustness and reliability of the proposed architecture in cluttered, dynamic and uncontrolled hospital scenarios.